Developing an Interactive Card as Media to Increase Students Vocabulary Mastery at Junior High School - Seliani Seliani; Jasuli Jasuli; Suhartatik Suhartatik (Universitas Muhammadiyah Gresik, 2022)
The present research is aiming at developing an interactive card as media to increase students’ vocabulary mastery at SMP PGRI 1 Wajak. The limited media and low vocabulary mastery are two main reasons why this research is conducted. This research is carried out through research and development adapted from R&D (Research and Development) of Borg and Gall which later has been adapted to the current needs. The development of this interactive card is carried out in several stages which cover: (1) need analysis, (2) planning, (3) product development, (4) expert validation, (5) product revision, (6) limited trials, (7) final product. The results of the validation of the material experts show the total score of 31 out of a maximum score of 35 with a precentage of 88%, and the criteria for the eligibility level show the precentage of 80 – 100%, then the product is classified as a valid qualification and suitable for use. From the validation results of media experts who are declared worthy and good to be tested on the audience.The trial was conducted to determine the feasibility of interactive card media based on audience assessment of 23 students of SMP PGRI 1 wajak. The trial was carried out by using the media in the learning process. The results of class trials for class VIII B SMP PGRI 1 Wajak show the total score of 718 from a maximum score of 750 with an average result of 95.73%, and the egibility level criteria show a percentage of 80 – 100%, then the product is classified as a valid qualification and suitable for use.